Description of Exclusive Breastfeeding to Babies in Java Island - Erna Martiyani; Farah Maulida Rahmah; Marisa Amalia Citra; Medinio Leonita KS (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Exclusive breastfeeding is that babies are only given breast milk, without the addition of other liquids such as formula milk, orange juice, honey, tea water, water, and without the addition of solid foods such as bananas, papaya, milk porridge, biscuits, rice porridge, and the team, as long as 6 months from the date of birth. Data from the World Health Organization (WHO) in 2016 still shows that the average rate of exclusive breastfeeding in the world is only around 38%. This study aims to determine the description of exclusive breastfeeding in infants in Java. Qualitative research using a descriptive observational study design that is conducting in-depth interviews with 4 informants which are by the interview guidelines. The results showed that the mother's age can affect the exclusive breastfeeding for the baby because the younger mother will produce more milk than the older mother. While the knowledge variable shows the results that mothers who have high knowledge about exclusive breastfeeding have a 20.8 times chance compared to mothers who have low knowledge. The existence of family support can also increase the mother's confidence in breastfeeding and the support from health workers can increase knowledge and motivate mothers to give exclusive breastfeeding. Based on this, we can say that breast milk is a perfect food that contains various nutrients that are needed by the body of living beings so that the body's metabolism can run smoothly and the development of the body goes well.